Tinjauan Yuridis Penetapan Nilai Jual Objek Pajak (NJOP) Sebagai Dasar Pengenaan Pajak Properti di Kota Pangkalpinang - Putri, Amelia Arianti; Hariansah, Syafri; Marhayani, Cik (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: The aim of this research is to analyze the juridical aspects related to the determination of NJOP and its impact on property tax imposition in the region. Metohodology: The method used is Empirical juridical research was conducted through a series of field interviews with respondents and informants. It also uses normative research, namely research through literature studies. Results: The results of this study will provide a deeper understanding of the legal framework governing the determination of NJOP and how it plays a role in determining the amount of property tax to be paid by taxpayers. It is expected that the results of this study can provide constructive input for the local government and related stakeholders to optimize the NJOP determination system and property tax imposition in order to achieve a balance between fair tax revenue and incentives for property development. Limitations: The analysis may be constrained by the existing legal framework and government policies at the time of the review. Changes in regulations or policies after the research is conducted can affect the validity of the findings. Contribution: Identifying and evaluating the appropriateness of the legal framework within the context of determining the Tax Object Sales Value (NJOP) in Pangkalpinang City, assists the government and stakeholders in rectifying or enhancing regulations that may impact properties